Using of concept “family” in kazakh lingvoculture - Amantay, Zh. B. (Journal of Oriental Studies, 2016)
In the article it was considered the conceptual content of concept family. The frequency of using lexeme of family in Kazakhlingvoculture was clarifi ed by sociolinguistic method of questioning.